Study of some Agronomic Aspects of Sabai Grass (Eulaliapsis binata Retz.) - Sharma, S. R.; Khera, A. S.; Bhullar, B. S. (Indian Forester, 1988)
Field investigations conducted on some agronomic aspects of Sabai grass at Punjab Agricultural University, Ludhiana revealed that wider row spacing (60 cm) increased both green and dry matter yields significantly over narrow spacing (30 cm). Out of twelve genotypes of Sabai grass studied, three genotypes viz., PBG-58, PBG-13 and PBG-36 were found to be high yielding and seem to be suitable for cultivation. The genotype-sparing and spacing-cutting interaction was significant.